Targeting glutamine metabolism sensitizes pancreatic cancer to PARP-driven metabolic catastrophe induced by ß-lapachone. Issue 1 (December 2015) - Chakrabarti, Gaurab; Moore, Zachary; Luo, Xiuquan; Ilcheva, Mariya; Ali, Aktar; Padanad, Mahesh; Zhou, Yunyun; Xie, Yang; Burma, Sandeep; Scaglioni, Pier; Cantley, Lewis; DeBerardinis, Ralph; et al.
Abstract Background Pancreatic ductal adenocarcinomas (PDA) activate a glutamine-dependent pathway of cytosolic nicotinamide adenine dinucleotide phosphate (NADPH) production to maintain redox homeostasis and support proliferation. Enzymes involved in this pathway (GLS1 (mitochondrial glutaminase 1), GOT1 (cytoplasmic glutamate oxaloacetate transaminase 1), andGOT2 (mitochondrial glutamate oxaloacetate transaminase 2)) are highly upregulated in PDA, and among these, inhibitors ofGLS1 were recently deployed in clinical trials to target anabolic glutamine metabolism. However, single-agent inhibition of this pathway is cytostatic and unlikely to provide durable benefit in controlling advanced disease. Results Here, we report that reducing NADPH pools by genetically or pharmacologically (bis-2-(5-phenylacetamido-1, 2, 4-thiadiazol-2-yl)ethyl sulfide (BPTES) or CB-839) inhibiting glutamine metabolism in mutant Kirsten rat sarcoma viral oncogene homolog (KRAS ) PDA sensitizes cell lines and tumors to ß-lapachone (ß-lap, clinical form ARQ761). ß-Lap is an NADPH:quinone oxidoreductase (NQO1 )-bioactivatable drug that leads to NADPH depletion through high levels of reactive oxygen species (ROS) from the futile redox cycling of the drug and subsequently nicotinamide adenine dinucleotide (NAD)+ depletion through poly(ADP ribose) polymerase (PARP ) hyperactivation.NQO1 expression is highly activated by mutantKRAS signaling. As such, ß-lap treatment concurrent with inhibition of glutamine metabolism in mutantKRAS, NQO1 overexpressing PDA leads to massive redox imbalance, extensive DNA damage, rapidPARP -mediated NAD+ consumption, and PDA cell death—features not observed inNQO1 -low, wild-typeKRAS expressing cells. Conclusions This treatment strategy illustrates proof of principle that simultaneously decreasing glutamine metabolism-dependent tumor anti-oxidant defenses and inducing supra-physiological ROS formation are tumoricidal and that this rationally designed combination strategy lowers the required doses of both agentsin vitro andin vivo . The non-overlapping specificities ofGLS1 inhibitors and ß-lap for PDA tumors afford high tumor selectivity, while sparing normal tissue.